2013
DOI: 10.1007/s00240-013-0621-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQoL) in cystine compared with non-cystine stone formers

Abstract: Cystinuria is a genetic cause of recurrent kidney stones which may be more recurrent and larger than more common non-cystine stones. They may have a greater impact on health-related quality of life (HRQoL). We measured this impact by surveying HRQoL in patients with stones, comparing non-cystine stone formers (NCSF) to cystine stone formers (CYSF) and both groups to normative values of the US population. We used SF-36v2 via an internet instrument. CYSF patients were recruited via cystinuria-related websites, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 13 publications
3
47
0
Order By: Relevance
“…Three US studies using this questionnaire compared stone formers to healthy adults and found lower scores in stone formers in two (general health perception and bodily pain), five (physical function, role limitations due to physical health problems, general health perception, social function and role limitations due to emotional problems) and six (all except role limitations due to emotional problems and mental health) of the eight domains, respectively 244246 . Among stone formers, one study reported that cystine stone formers had the worst QOL owing to role limitations caused by emotional problems 247 . When comparing scores between men and women, most of the studies reported lower QOL in female stone formers 244247 .…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Three US studies using this questionnaire compared stone formers to healthy adults and found lower scores in stone formers in two (general health perception and bodily pain), five (physical function, role limitations due to physical health problems, general health perception, social function and role limitations due to emotional problems) and six (all except role limitations due to emotional problems and mental health) of the eight domains, respectively 244246 . Among stone formers, one study reported that cystine stone formers had the worst QOL owing to role limitations caused by emotional problems 247 . When comparing scores between men and women, most of the studies reported lower QOL in female stone formers 244247 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Among stone formers, one study reported that cystine stone formers had the worst QOL owing to role limitations caused by emotional problems 247 . When comparing scores between men and women, most of the studies reported lower QOL in female stone formers 244247 . However, these results have to be interpreted with caution because the timing of the questionnaire in relation to the last stone event has a significant effect on the SF-36 score.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Further, her chronic pain was often downplayed and not always taken seriously if an obstructing stone was not seen on imaging studies. Understanding the chronic nature of cystinuria and recognizing that these patients have real pain may help improve the quality of care for patients with cystinuria (Modersitzki, Pizzi, Grasso, & Goldfarb, 2014). …”
Section: Case Studymentioning
confidence: 99%
“…Although many studies have been published about the development of new treatment methods or the efficiency of treatment, few studies have focused on QoL of patients with urinary stone. The importance of QoL for patients with urinary stone has recently begun to be acknowledged and several studies have been published up to date [5][6][7][8][9][10][11][12][13][14][15][16][17]. With increasing interest in QoL of patients with urinary stone, research has also focused on how to evaluate QoL more accurately.…”
Section: Introductionmentioning
confidence: 99%